Crack detection on sheared-edge of ultra-high strength steel sheet by using acid immersion - Azzmer, S.; Jaafar, H.; Tajul, Liyana; Sulaiman, Mohd Hafis; Zainal Abidin, Zailani (IOP Publishing Ltd, 2020)
t. In trimming of ultra-high strength steel (UHSS) sheet, the high strength of the sheet usually results in large fracture and low burnish surfaces on the sheared-edge. For metal stamping industries, large fracture surfaces are unwanted, as it not only deteriorates shearededge quality but also leads to delayed-crack. In this study, crack detection by using acid immersion on the sheared-edge of ultra-high strength steel sheet caused by the trimming process was investigated. The ultra-high strength steel sheet of JSC780YN, JSC980YN, and JSC1180YN having different strengths were trimmed and immersed in 35% hydrochloric acid under a controlled time interval. The steel sheet with higher strength was found to produce larger fracture surface after trimming, i.e. more than 50% of the entire sheared-edge is fracture surface. Besides, the larger fracture surface of the steel sheet results in higher crack exposure and higher crack propagation, which in the long run, it can cause failure to the part manufactured using UHSS.